The effect of two types of resorbable augmentation materials – a cement and an adhesive – on the screw pullout pullout resistance in human trabecular bone. (October 2020) - Wu, Dan; Pujari-Palmer, Michael; Bojan, Alicja; Palmquist, Anders; Procter, Philip; Öhman-Mägi, Caroline; Ferguson, Stephen J.; Isaksson, Per; Persson, Cecilia
Abstract: Augmentation materials, such as ceramic and polymeric bone cements, have been frequently used to improve the physical engagement of screws inserted into bone. While ceramic, degradable cements may ultimately improve fixation stability, reports regarding their effect on early fixation stability have been inconsistent. On the other hand, a newly developed degradable ceramic adhesive that can bond with tissues surrounding the screw, may improve the pullout performance, ensure early stability, and subsequent bony integration. The aim of this study was to investigate failure mechanisms of screw/trabecular bone constructs by comparing non-augmented screws with screws augmented with a calcium phosphate cement or an adhesive, i.e. a phosphoserine-modified calcium phosphate. Pullout tests were performed on screws inserted into trabecular cylinders extracted from human femoral bone. Continuous and stepwise pullout loading was applied with and without real-time imaging in a synchrotron radiation micro-computed tomograph, respectively. Statistical analysis that took the bone morphology into account confirmed that augmentation with the adhesive supported significantly higher pullout loads compared to cement-augmented, or non-augmented screws. However, the adhesive also allowed for a higher injection volume compared to the cement. In-situ imaging showed cracks in the vicinity of the screw threads in all groups, and detachment of the augmentation materials from the trabecular bone in the augmented specimens. Additional cracks at the periphery of the augmentation and the bone-material interfaces were only observed in the adhesive-augmented specimen, indicating a contribution of surface bonding to the pullout resistance. An adhesive that has potential for bonding with tissues, displayed superior pullout resistance, compared to a brushite cement, and may be a promising material for cementation or augmentation of implants.